Study of Cytotoxic Effects of Saffron in MCF-7 Cells: Cytotoxicity of saffron - Seyed Hadi Mousavi,; Jalil Tavakkol Afshari,; Azam Brook, (Iranian Journal of Pharmaceutical Sciences, 2008)
Current therapies for breast cancer are often limited by short-term efficacy due to the emergence of drug resistance. There has been increased interest in the use of naturally occurring compounds with chemopreventive and chemotherapeutic effects in the treatment of cancers. Saffron, dry stigmas Crocus sativusL., used in Iran as a spice, is known for its anticancer properties. In this study, the cytotoxic and apoptogenic effects of saffron in MCF-7 cells as an in vitromodel for breast cancer study were investigated. Meanwhile role of caspases were studied in its toxicity. MCF-7 and L929 cell lines were cultured in DMEM medium and incubated with different concentrations of saffron extract (100 to 2000 μg/ml). Cell viability was assessed by MTTassay. Apoptotic cells were determined using PI staining of DNA fragmentation by flow cytometry (sub-G1 peak). Role of caspase were studied using the pan-caspase inhibitor, z-VAD-fmk. Saffron extract decreased cell viability in MCF-7 cells as a concentration- and time-dependent manner. Doses of saffron inhibited 50% cell growth (IC50) against MCF-7 was 400 μg/ml after 48 h of incubation. Saffron could induce apoptosis in MCF-7 cells in which apoptosis was dependent on caspase activation. It might be concluded that saffron could cause MCF-7 cell death, in which apoptosis or programmed cell death play an important role.Saffron could be also considered as a promising chemotherapeutic agent in breast cancer treatment.